PEREKAYASAAN MODEL PEMBELAJARAN BENGKEL SASTRA UNTUK MENINGKATKAN KEMAMPUAN SISWA SEKOLAH DASAR DALAM MENULIS KARYA SASTRA - Rohayati, Etty; Kurniawati, -; Ernalis, - (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2017)
Abstract: The purpose of this study was to explore and describe (1) the engineering design of a literary workshop models that appropriately applied to primary school students in learning writing literary works; (2) the effectiveness of the application of the model of literary workshops that have been engineered for increased ability to write literature in primary school students; and (3) the most dominant factor supporting the ability of elementary school students in writing literary works through the implementation of a literary workshop models that have been engineered. This study was conducted using a combination of the type of explanatory research. The subjects were elementary school students in the county and the city of Bandung. The research sample will be selected by using the sampling area. Research data will be collected using a variety of instruments. Research data will be processed using the quantitative data processing techniques to test the statistical and qualitative data analysis techniques. The study concluded that the model of a literary workshop for elementary school students performed at different stages with the stages of this model when used for students that consists of 9 stages. Based on the results of its implementation can be argued that there are significant differences between students' ability to write prose experimental class control class. This means that the application of the influential literary workshops and contribute to enhancing the student's ability to write prose. Further it can also be concluded that based on the results of the analysis of the case can be concluded that the main factors that affect the student's ability to write prose can be categorized into three main categories: (1) understanding the intrinsic elements of prose, (2) the habit of writing, and (3) practice and guidance writing ..Keywords: the ability to write prose, literary workshop models, elementary school students Abstrak: Tujuan penelitian ini adalah untuk menggali dan memaparkan (1) perekayasaan desain model bengkel sastra agar tepat diterapkan pada siswa sekolah dasar dalam pembelajaran menulis karya sastra; (2) keefektifan penerapan model bengkel sastra yang telah direkayasa bagi peningkatan kemampuan menulis karya sastra pada siswa sekolah dasar; dan (3) faktor yang paling dominan mendukung kemampuan siswa sekolah dasar dalam menulis karya sastra melalui penerapan model bengkel sastra yang telah direkayasa. Penelitian ini dilaksanakan dengan menggunakan metode penelitian kombinasi jenis eksplanatori. Subjek penelitian ini adalah siswa sekolah dasar di di Kabupaten dan Kota Bandung. Sampel penelitian akan dipilih dengan teknik area sampling. Data Penelitian akan dikumpulkan dengan menggunakan berbagai instrumen. Data hasil penelitian akan diolah dengan menggunakan teknik pengolahan data kuantitatif yakni dengan uji statistika dan teknik analisis data kualitatif. Penelitian ini menyimpulkan bahwa model bengkel sastra untuk siswa sekolah dasar dilakukan dengan tahapan yang berbeda dengan tahapan model ini ketika digunakan untuk mahasiswa yakni terdiri atas 9 tahapan. Berdasarkan hasil implementasinya dapat dikemukakan bahwa terdapat perbedaan yang signifikan antara kemampuan menulis prosa siswa kelas eksperimen dengan kelas kontrol. Hal ini berarti penerapan model bengkel sastra berpengaruh dan berkontribusi positif bagi peningkatan kemampuan siswa menulis prosa. Lebih lanjut dapat pula disimpulkan bahwa berdasarkan hasil analisis kasus dapat disimpulkan bahwa  faktor utama yang memengaruhi kemampuan siswa menulis prosa dapat dikategorikan menjadi 3 kategori utama yakni (1)  pemahaman unsur intrinsik prosa, (2)  kebiasaan menulis, dan (3)  latihan dan bimbingan penulisan..Kata Kunci: kemampuan menulis prosa, model bengkel sastra, siswa sekolah dasar